Sensitivities of an endemic, endangered California smelt and two non-native fishes to serial increases in temperature and salinity: implications for shifting community structure with climate change. Issue 1 (18th February 2019) - Davis, Brittany E; Cocherell, Dennis E; Sommer, Ted; Baxter, Randall D; Hung, Tien-Chieh; Todgham, Anne E; Fangue, Nann A
Abstract : This study showed that in three quite different fish species from the San Francisco Estuary, stress from elevated temperature or salinity did not reduce their ability to cope with subsequent stressors. Abstract: In many aquatic systems, native fishes are in decline and the factors responsible are often elusive. In the San Francisco Estuary (SFE) in California, interactions among native and non-native species are key factors contributing to the decline in abundance of endemic, endangered Delta Smelt ( Hypomesus transpacificus ). Climate change and drought-related stressors are further exacerbating declines. To assess how multiple environmental changes affect the physiology of native Delta Smelt and non-native Mississippi Silverside ( Menidia beryllina ) and Largemouth Bass ( Micropterus salmoides ), fishes were exposed to serial exposures of a single stressor (elevated temperature or salinity) followed by two stressors (elevated temperature and salinity) to determine how a single stressor affects the capacity to cope with the addition of a second stressor. Critical thermal maximum (CTMax; a measure of upper temperature tolerance) was determined after 0, 2, 4 and 7 days following single and multiple stressors of elevated temperature (16°C vs. 20°C) and salinity (2.4 vs. 8–12 ppt, depending on species). Under control conditions, non-native fishes had significantly higher CTMax than the native Delta Smelt. An initial temperature or salinity stressor did not negatively affect the ability of any species to tolerate a subsequent multiple stressor. While elevated salinity had little effect on CTMax, a 4°C increase in temperature increased CTMax. Bass experienced an additive effect of increased temperature and salinity on CTMax, such that CTMax further increased under multiple stressors. In addition, Bass demonstrated physiological sensitivity to multiple stressors demonstrated by changes in hematocrit and plasma osmolality, whereas the physiology of Silversides remained unaffected. Non-native Bass and Mississippi Silversides showed consistently higher thermal tolerance limits than the native Delta Smelt, supporting their abundance in warmer SFE habitats. Continued increases in SFE water temperatures predicted with climate change may further impact endangered Delta Smelt populations directly if habitat temperatures exceed thermal limits.